Non-performing Financing and Rate of Return on Mudharaba and Musharaka Contracts of Islamic Banks Before and During the COVID-19 Period - Ahmad Fatoni; Maidah Siswati; Kurnia Dwi Sari Utami (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
The purpose of this study is to evaluate whether there are differences in non-performing financing and yield rates on mudharaba and musharaka financing of Islamic commercial banks in Indonesia, both before and during the COVID-19 pandemic. This study uses a quantitative method using a sample of 14 Islamic commercial banks in Indonesia. The data used is monthly secondary data obtained from Islamic banking statistics for 2017-2022. Data analysis was carried out using the Kolmogorov-Smirnov Test normality test and the Wilcoxon Signed Rank Test non-parametric difference test using IBM SPSS 26 software. The results showed differences in non-performing financing and the rate of return on mudharaba and musharaka financing in the period before and during the COVID-19 pandemic.